Difficult Airway in Adult patients: Outcome and institutional response - Martínez López, Ángel Roberto; Carías, Alejandro; Auza-Santivañez, Jhossmar Cristians; Perez-Aramayo, Gustavo; Mamani-Manzaneda, Laura Pamela; Mayta-Amador, Pablo Saul; Apaza-Huanca, Blas (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction. The airway is one in which a trained anesthesiologist experiences difficulty in ventilation or difficulty in intubation, or both. Objective. To determine the outcome of patients over 18 years of age with a difficult airway and the characteristics of the institutional response capacity, at the Hospital Escuela Universitario, Tegucigalpa, Honduras. 2018-2020. Methods. Descriptive Cross-Sectional Study, with a sample of 80 patients with difficult airway. Non-probability sampling for convenience. The data were entered in EPI-INFO. Descriptive analysis was performed as measures of central tendency and grouping. The proportion was estimated using the formula: P = Number of people with difficult airways / number of patients older than 18 years multiplied by 100. The protocol was approved by the Ethics Committee in Biomedical Research / FCM / UNAH. Results. 28,8 % had ASA II anesthetic risk, 27,6 % had ASA IIE. 68,5 % had Grade III Cormack Lehane Scale, 7,5 % Grade II, 23,7 % Grade IV, 97,5 % of the intubation was successful, 2,5 % was unsuccessful. 36,3 % with a difficult airway are overweight, 25 % are type I obese, 13,8 % are type III obese and 8,3 %. There was 97,2 % of successful intubation and, in most, up to 2 attempts were required to achieve it. Conclusions. Obesity constitutes a risk factor for difficult ventilation and intubation, as well as an anesthetic risk. ASA II and III is also a risk factor for difficult airway.